The Role of Community Pharmacy Personnel in Tuberculosis Case Detection: A Narrative Review - Carla Florencia; Ida Ayu Andri Parwitha; Dian Ayu Eka Pitaloka; Ivan Surya Pradipta (Faculty of Mathematic and Natural Science, Garut University, 2026)
Tuberculosis (TB) continues to pose a global health challenge, mainly due to low case detection rates in high-burden countries like Indonesia. Community pharmacies (CP), the health facilities most commonly visited by individuals experiencing tuberculosis symptoms, play an essential role in early detection and referral to health facilities. This narrative review examines the role of community pharmacists in TB case detection through pharmacy-based interventions in developing countries with high TB burden. The following databases were used to identify articles that met the inclusion and exclusion criteria: PubMed and Scopus. Based on three eligible studies from India, Pakistan, and Cambodia, pharmacy-based TB case detection programs were associated with increased case detection and referral of presumptive TB cases. The included studies reported that structured interventions, including pharmacist training, referral systems, monitoring, and public-private collaboration, may support TB case detection in high-burden settings. However, several barriers were identified, including uncertainty about referral pathways, financial constraints, and concerns about service quality at referral facilities. Given the limited evidence from only three studies, these findings should be interpreted cautiously, and further research is needed to assess the effectiveness and sustainability of pharmacy-based TB case-detection programs. CP engagement may contribute to TB case detection when reinforced by well-defined, structured referral pathways and integration with public-private TB control initiatives.